In vitroandin vivo antibacterial activities of rhizophora man-gle l. against helicobacter pylori. chemical compounds elucida-tion - Luz MarÃa, SÃ¡nchez Perera; MarÃa Rosario, Morales Espinosa; Guillermo, Delgado Lamas; Sergio, de MendonÃ§a; Diego Miguel, Cortes; Rafael, RamÃrez Miranda (International Journal of Pharmacology and Toxicology, 2017)
Rhizophora mangle L. is a vegetal species widely distributed in Cuba and other Caribbean countries with ethno- pharmacology relevance and preview reports as antiulcer and wound healing properties. The present work describes the in vitro and in vivo antibacterial activities of dried aqueous extract of bark and polyphenol fractions from R. mangle against Helicobacter pylori and the identification of new compounds in the active extracts. Minimum inhibitory concentration (MIC) and Minimum bactericide concentration (MBC) were evaluated against reference and clinical Helicobacter pylori strains with total extract, High Molecular Weight and Low Molecular Weight fractions isolated from total extract. Positive active fractions in vitro tests were evaluated in vivo using H. pylori C57BL/6 mice. Fractionation, isolation and structural elucidation of the compounds on High Molecular Weigh fraction and on Low Molecular Weight fraction were made using Chromatography methods and Mass and H+NMR spectrometry. Total aqueous extract from bark of R. mangle and some fraction shown promissory antibacterial activity on in vitro and in vivo models. It was isolated and identified proantocyanidin, catechin and epicatechin derivates, cyanidin and other compounds in this promissory extract. These results appoint to total extract with a promissory active principle in the development of phytodrug with antibacterial effect and as proton pump inhibitor by the treatment of gastroduodenal ulcer.